Multilingual Practices of Senegalese Immigrants in Rome: Construction of Identities and Negotiation of Boundaries. (September 2015) - Smith, Maya
<x content-type="archive" xml:space="preserve">Abstract</x> While African immigrants and Italians of African descent have become more visible in Italian society since the 1980s, Italian culture and identity are still largely understood by majority white Italians in terms of race, nationhood, and family history. Overwhelmingly absent from these national discussions concerning the inclusion of immigrants, foreign residents, and so-called non-Italian citizens in society are the very people at the center of these debates. To give voice to some of these individuals, this article explores how a specific group, the Senegalese community in Rome, conceptualizes and understands identity formation as foreigners and as linguistic, racial and ethnic minorities through the lens of Applied Linguistics. Through analysis of code-switching in qualitative ethnographic data collected in the spring of 2010, I show how multilingual practices illustrate these immigrants' understandings of inclusion/exclusion and how these notions intersect with ideas about blackness. Therefore, this essay calls into question the static, exclusionary narrative on national identity and shows the ways in which the Senegalese community in Rome inserts formulations of blackness in the conversation. By comprehending how immigrants perceive their identities and the sites in which these identities are constructed, we gain a more multifaceted perspective on what it means to be Italian.